Contribuições ao estudo comparativo dos efeitos de descargas atmosféricas em sistemas compostos por cabos aéreos e subterrâneos a seco e a óleo - Onuki, Alexandre Shozo (2009)
By means of computing simulations, it is presented in this work a comparative study of the effects of electromagnetic transients proceeding from indirect and direct atmospheric discharges in mixed-transmission lines, which consist of aerial and underground parts with oil and dry type isolation. The developed and implemented model in the ATP computing environment was based on a part of AES- Eletropaulo subtransmission system compounded of Bandeirante substation and Morumbi, Granja Julieta and Alto da Boa Vista distribution stations. The data of the considered equipment were first obtained through a R&D project regarding the effects of atmospheric discharges in Distribution and Transmission Stations developed for energy distribution company AES-Eletropaulo by Uberlândia Federal University and Santa Cecília University. Thus, equipment equivalent models development was done individually and based on real data. Data input consistency checking was based on either measured or theoretical values, depending on the information available. The equivalent electric system configurations used in simulations were determined by several combinations which considered the alternance of parameters, such as: types of cable, use of lightning rods and kind of cables installations (kept unmodified in relation to the rest of the system). In relation to transients effects attenuation, the main results found were the following: better results of oil cables than that of dry cables; small influence of systemic alterations of the electric distribution stations; efficiency of lightning rods usage in this type of system and small variations for the provision of cables.